Preparation of Whey Protein-Oligosaccharide Complex and Its Application as Fat Substitute in Processed Cheese - LI Qianwen, LIANG Ying, WANG Xiaonan, ZHANG Chuan, LIU Zhiqin, CHEN Shuxing, LÜ Mingqi (Shipin Kexue, 2023)
Glycosylated whey protein (GWP) was prepared from whey protein and xylooligosaccharide by wet glycosylation method. Its advantages for use as a fat substitute were analyzed, and the application of this fat substitute in reduced-fat processed cheese was explored. The results showed that the optimal preparation conditions were determined as: xylooligosaccharide concentration of 6%, reaction temperature of 85 ℃ and reaction time of 2 h. The grafting degree of GWP prepared using these conditions was (29.28 ± 1.53)%, and a browning phenomenon occurred during the preparation process. Compared with whey protein, the contents of α-helix, β-fold, β-turn and random coil structures changed in GWP, and the water and oil-holding properties increased by 60.18% and 103.97%, respectively; the emulsifying capacity and emulsion stability increased by 30.81% and 13.57%, respectively. The surface of GWP was smoother. The surface hydrophobicity at pH 7.0 was 2.48 times higher than that of whey protein. After shearing at 10 000 r/min for 10 minutes, the median particle diameter of GWP was 7.57 µm, and the stability of the solution was obviously improved, so that GWP could be used to simulate fat. The hardness of reduced-fat processed cheese with 60% butter replacement by GWP was significantly lower than that of full-fat processed cheese (P 0.05), and the total sensory score was equivalent to that of full-fat processed cheese. These results proved that the glycosylated whey protein has a potential application as a fat substitute in reduced-fat food while guaranteeing that the quality of the product is good.